The Use of English by Malaysian Business Executives in the Commercial Sector - Goh, Sharon Seng Pang; Chan, Swee Heng (Universiti Putra Malaysia Press, 1996)
This study is part of a larger survey on the issue of the importance and extent of the use of the English language in the Malaysian economy. While the use of English has often been said to be important, large-scale studies to support and to provide details about the situation are lacking. This present study presents information from the perspective of business executives who use the English language in their jobs. The data obtained confirm the importance of the use of the English language in the commercial work-place. The business executives claim to have confidence in the use of the language. Thus potential employees must also achieve a level of proficiency that would enable them to use the--language confidently and efficiently. The most frequent language sub-skills used are: listening to social conversations in business, speaking on the telephone, reading and writing routine letters and memos. In terms of order of importance, speaking was ranked the highest. This attachment of importance to speaking suggests that job success is very much related to the ability to speak well. This information would have deep implications for education and training programmes